U.S. Government and FED bailout plans in times of financial crisis - Savkanič, Tomáš (2011)
Since current financial crisis, U.S. government and Federal Reserve have vigorously commenced several bailout plans in order to avert cataclysmic financial meltdown, stabilize financial markets, constrain bank failures, and inhibit a credit freeze. Although the policies financed by taxpayer funds were originally estimated at $700 billion, they swiftly turned into over $15 trillion. This circumstance have naturally arisen a wave of critique doubting the necessity of government interventions. The negative feedbacks are based on capitalism rules where failure of weaker banks and companies is an essential and natural aspect of market. The thesis aim is to analyze the programs necessity, efficiency and effectiveness using methods such as cost-benefit analysis. In conclusion, this thesis will try to answer how efficacious the federal government bailout plans will be in the long run, even though they can seem auspicious in ameliorating present situation in the short run.